Energy absorbtion capability of damage affected composite structures - Ribeaux, Michael (2003)
The aim of this project is to consider the effect of damage on the energy absorption potential of continuous filament random mat (CoFRM) E-glass / polyester composite tubes. Composite materials have been shown to absorb significantly higher specific energy levels than metals under axial crushing conditions. This property can be exploited in automotive crashworthiness applications. Replacing steel crash structures with composites can lead to significant weight reductions. However, damage in composite structures can be difficult to assess and may not be visible by casual inspection. There is a concern that damage may accumulate in the crash structures, as a result of in-service wear and tear or due to operator negligence. It is important to understand how much accidental damage the crash structures can sustain before they are no longer able to fulfil their requirements. Two wall thicknesses of circular and square tube geometries were tested, with over 650 samples crushed either quasi-statically at 5mm/min or dynamically at 5m/s. Damage was induced in three ways: drilled holes, delamination in the form of Melinex® inserts moulded into the samples, and out-of-plane impact damage of various energy levels.